3+5+6+3+6+5+3+7+5+1111111111111111111111111111111111111111+2=
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
5: \(=3-\dfrac{1}{4}+\dfrac{2}{3}-5+\dfrac{1}{3}+\dfrac{6}{5}-6+\dfrac{7}{4}-\dfrac{3}{2}\)
\(=3-5-6+\dfrac{-1}{4}+\dfrac{7}{4}+\dfrac{2}{3}+\dfrac{1}{3}+\dfrac{6}{5}-\dfrac{3}{2}\)
\(=-8+\dfrac{3}{2}+1+\dfrac{-3}{10}\)
\(=-7+\dfrac{15-3}{10}=-7+\dfrac{6}{5}=-\dfrac{29}{5}\)
6: \(=6-\dfrac{2}{3}+\dfrac{1}{2}-5-\dfrac{5}{3}+\dfrac{3}{2}-3+\dfrac{7}{3}-\dfrac{5}{2}\)
\(=6-5-3-\dfrac{2}{3}-\dfrac{5}{3}+\dfrac{7}{3}+\dfrac{1}{2}+\dfrac{3}{2}-\dfrac{5}{2}\)
\(=-2-\dfrac{1}{2}=-\dfrac{5}{2}\)
7: \(=\dfrac{5}{3}-\dfrac{3}{7}+9-2-\dfrac{5}{7}+\dfrac{2}{3}+\dfrac{8}{7}-\dfrac{4}{3}-10\)
\(=9-2-10+\dfrac{5}{3}+\dfrac{2}{3}-\dfrac{4}{3}+\dfrac{-3}{7}-\dfrac{5}{7}+\dfrac{8}{7}\)
=-3+1
=-2
8: \(=8-\dfrac{9}{4}+\dfrac{2}{7}+6+\dfrac{3}{7}-\dfrac{5}{4}-3-\dfrac{2}{4}+\dfrac{9}{7}\)
\(=8+6-3+\dfrac{2}{7}+\dfrac{3}{7}+\dfrac{9}{7}-1-\dfrac{2}{4}\)
\(=11+2-1-\dfrac{1}{2}\)
=11+1/2
=11,5
\(\dfrac{2}{5}+\dfrac{2}{3}+\dfrac{2}{4}\)
= \(\dfrac{24}{60}\) + \(\dfrac{40}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{64}{60}\) + \(\dfrac{30}{60}\)
= \(\dfrac{47}{30}\)
\(\dfrac{2}{6}+\dfrac{3}{12}\)
= \(\dfrac{4}{12}\) + \(\dfrac{3}{12}\)
= \(\dfrac{7}{12}\)
\(\dfrac{5}{6}\) + \(\dfrac{1}{3}\)
= \(\dfrac{5}{6}\) + \(\dfrac{2}{6}\)
= \(\dfrac{7}{6}\)
\(\dfrac{1}{3}\) + \(\dfrac{5}{12}\) + \(\dfrac{5}{6}\)
= \(\dfrac{4}{12}\) + \(\dfrac{5}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{9}{12}\) + \(\dfrac{10}{12}\)
= \(\dfrac{19}{12}\)
\(\dfrac{5}{8}\) + \(\dfrac{4}{7}\)
= \(\dfrac{35}{56}\) + \(\dfrac{32}{56}\)
= \(\dfrac{67}{56}\)
\(\dfrac{7}{3}\) + \(\dfrac{8}{7}\)
= \(\dfrac{49}{21}\) + \(\dfrac{24}{21}\)
= \(\dfrac{73}{21}\)
\(\dfrac{1}{5}+\dfrac{5}{35}\)
= \(\dfrac{7}{35}\) + \(\dfrac{5}{35}\)
= \(\dfrac{12}{35}\)
a: 14/5-7/5=7/5
b: 7/8-1/3+5/4
=21/24-8/24+30/24
=43/24
c; =7/6+5/6+2/15+13/15
=2+1
=3
d: =4*5/3*11=20/33
e: =2/9*1/6*1/4=2/9*1/24=1/108
2:
a: \(=\dfrac{3}{9}\cdot\dfrac{4}{4}\cdot\dfrac{5}{5}\cdot\dfrac{6}{6}\cdot\dfrac{7}{7}=\dfrac{1}{3}\)
b: \(=\dfrac{1}{6}\left(\dfrac{22}{3}-\dfrac{2}{3}\right)=\dfrac{10}{3}\cdot\dfrac{1}{6}=\dfrac{10}{18}=\dfrac{5}{9}\)
c; \(=\dfrac{1}{3}\left(9-\dfrac{2}{5}-\dfrac{3}{5}\right)=\dfrac{8}{3}\)
\(\dfrac{8}{9}:\dfrac{3}{7}=\dfrac{56}{27}\\ \dfrac{8}{9}+\dfrac{2}{5}=\dfrac{58}{45}\\ \dfrac{7}{8}-\dfrac{1}{3}=\dfrac{13}{24}\\ \dfrac{3}{10}\times\dfrac{1}{6}=\dfrac{1}{20}\\ 1\dfrac{2}{7}+6\dfrac{5}{6}=\dfrac{9}{7}+\dfrac{41}{6}=\dfrac{341}{42}\\ 5\dfrac{3}{4}-\dfrac{1}{5}=\dfrac{23}{4}-\dfrac{1}{5}=\dfrac{111}{20}\\ 6\dfrac{2}{9}:4\dfrac{7}{10}=\dfrac{56}{9}:\dfrac{47}{10}=\dfrac{560}{423}\\ \dfrac{5}{3}+\dfrac{3}{2}-\dfrac{7}{6}=2\)
2) -3(4 - 7) + 5(-3 + 2)
= -3.4 + 3.7 - 5.3 + 5.2
= -12 + 21 -15 + 10
= 31 - 27
= 4
4) -5(2 - 7) + 4(2 - 5)
= -5.2 + 5.7 + 4.2 - 4.5
= -10 + 35 + 8 - 20
= 38 - 30
= 8
3: \(=20-12-8+12=20-8=12\)
5: \(=-18-42-21-35=-116\)
3: \(=-15+18-12+8=-27+26=-1\)
2: \(=-12+21-15+10=9-5=4\)
76875787